2006
DOI: 10.1111/j.1365-2028.2006.00672.x
|View full text |Cite
|
Sign up to set email alerts
|

Population density, structure and early growth characteristics of Tarchonanthus camphoratus in a woodland at Naivasha, Kenya

Abstract: A study on population density, structure, distribution and early growth characteristics of Tarchonanthus camphoratus was carried out on a Tarchonanthus-dominated woodland. A line plot transect 4 km in length was laid out in a woodland along the altitudinal gradient capturing most of the observed vegetation variation. In total 34, 20 · 20 m plots were evaluated for their horizontal population structure and species composition. In addition, six more plots dominated by Tarchonanthus were monitored for coppice and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Tarchonanthus camphoratus reproduces vegetatively and has small winddispersed seeds (Noad & Bernie, 1989;Coates-Palgrave, 2002); this together with its hardy characteristics and aggressive resprouting behaviour after disturbance, e.g. by fire, makes it a potential bush encroacher, particularly in disturbed habitats as other studies have shown (Kiruki & Njung'e, 2007). We predict that overgrazing by livestock facilitates net recruitment of T. camphoratus.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Tarchonanthus camphoratus reproduces vegetatively and has small winddispersed seeds (Noad & Bernie, 1989;Coates-Palgrave, 2002); this together with its hardy characteristics and aggressive resprouting behaviour after disturbance, e.g. by fire, makes it a potential bush encroacher, particularly in disturbed habitats as other studies have shown (Kiruki & Njung'e, 2007). We predict that overgrazing by livestock facilitates net recruitment of T. camphoratus.…”
Section: Introductionmentioning
confidence: 79%
“…In a study to characterize population density, structure and early growth characteristics of T. camphoratus, Kiruki & Njung'e (2007) also found that regeneration is the highest in more disturbed habitats especially those experiencing exploitation through tree cutting, establishment of footpaths and charcoal burning kilns. In our study site, exploitation of T. camphoratus was less clear, but our disturbed site contained well-trodden footpaths and there was evidence of extensive trampling and overgrazing by livestock.…”
Section: Discussionmentioning
confidence: 99%
“…Tarchonanthus camphoratus is drought resistant and associated with earlysuccessional species, such as Acacia species, and dominates East Africa woodlands (e.g. Kiruki and Njung'e 2007). The disturbance tolerant species, A. etbaica and C. purpurea are fast growing species and a previous study has shown that fast growing species in some cases can assure ecosystem resilience (MacGillivray et al, 1995).…”
Section: Discussionmentioning
confidence: 98%
“…The latter taxa are associated with fire. Tarchonanthus camphoratus regenerates very well after disturbance by cutting or fire (Kiruki and Njung'e, 2007), Artemisia afra often colonizes burnt areas in mountains (Beentje, 1994), Protea grows in mountainous grasslands that are burnt, and Hymenocardia acida is also fire hardy (White, 1983). However, there is no increase in the amount of charcoal particles relative to the amount of pollen and spores.…”
Section: Holocenementioning
confidence: 99%